Modeling the Revenue and Distributional Effects of Tax Reform in Paraguay : Challenges and Lessons - Canavire, Gustavo; Corral, Paul; Farfan, Gabriela; Galeano, Juan Jose; Gayoso, Lyliana; Piontkivsky, Ruslan; Sacco, Flavia (World Bank, Washington, DC, 2021)
In 2019, the Government of Paraguay (GOP) embarked on a comprehensive tax reform to simplify and modernize its tax system. At the request of the Ministry of Finance (MOF), and building on long-standing policy dialogue with the country, the World Bank (WB) Poverty team worked quickly to develop a micro-simulation tool to inform policymakers on the potential revenue and distributional effects of the reform as it was being developed. In this note, we summarize the context, approach, challenges, and lessons learned from constructing the Fiscal Simulation Tool and highlight the tool’s long-term value for policy dialogue and decision making.